1992
DOI: 10.4269/ajtmh.1992.47.291
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Schistosoma Haematobium Infection on the Iron Status of Schoolchildren in Niger

Abstract: The relationship between iron status and degree of infection by Schistosoma haenzatobium was studied in 174 schoolchildren from Niger in an area endemic for urinary schistosomiasis. Iron deficiency was defined by a combination of three reliable indicators: a low serum ferritin level combined with a low transferrin saturation, a high erythrocyte protoporphyrin level, or both. Hematuria and proteinuria were found in 76.4% and 79.9% of the children, respectively, while 95.4% excreted eggs (geometric mean egg coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 9 publications
3
21
0
2
Order By: Relevance
“…Studies conducted elsewhere have indicated folate deficiency in undernourished children (47) living under similar conditions. Urinary schistosomiasis in this study was strongly associated with anemia-a finding also shown in other studies conducted elsewhere (32,48). Schistosomiasis, whether intestinal or urinary, may be associated with blood loss that can cause a loss of up to 6 mg Fe/d (42,48).…”
Section: Diseases As a Risk Factor For Iron Deficiency Anemiasupporting
confidence: 72%
“…Studies conducted elsewhere have indicated folate deficiency in undernourished children (47) living under similar conditions. Urinary schistosomiasis in this study was strongly associated with anemia-a finding also shown in other studies conducted elsewhere (32,48). Schistosomiasis, whether intestinal or urinary, may be associated with blood loss that can cause a loss of up to 6 mg Fe/d (42,48).…”
Section: Diseases As a Risk Factor For Iron Deficiency Anemiasupporting
confidence: 72%
“…More than a half of the investigated school children had parasitic infections and older children appeared to be most affected. Hookworm and schistosomiasis, which have been found to correlate significantly with anaemia in these children, are the main causes of haemorrhagic anaemia (Prual et al, 1992). These infections have been an implicated cause of anaemia in many parts of the developing world (Bhargava et al, 2003).…”
Section: Figure 1: Proportion Of Children Provided With Breakfast (Bfmentioning
confidence: 98%
“…In areas where iron deficiency is also enhanced by increased gastrointestinal blood loss due to hookworm infection (Layrisse & Roche, 1964) or by schistosomiasis (Prual et al 1992), programmes to reduce the prevalence of these infections should be part of the effort to control iron deficiency. Parasite control will not be specifically discussed in this overview but this should certainly not be interpreted as a downgrading of the importance of these interventions, but rather as a recognition that it would require another survey.…”
Section: Intervention Options For the Alleviation O F I R O N Deficiencymentioning
confidence: 99%